G-Protein-Coupled Estrogen Receptor (GPER) in Inflammatory Myopathies - Delia Righi; Diego Lopergolo; Nila Volpi; Daniela Franci; Paola Lorenzoni; Margherita Aglianò; Gianna Berti; Carlo Manco; Nicola De Stefano; Federica Ginanneschi (Neurology International)
Background/Objectives: Given the multifaceted role of estrogen hormones in skeletal muscle pathophysiology and their well-established immunomodulatory properties, this study aimed to characterize the expression of the G-protein-coupled estrogen receptor (GPER) in patients with inflammatory myopathies (IM). Methods: Immunohistochemical analysis was performed on muscle biopsies from 13 patients with IM, 11 with non-inflammatory myopathies (N.IM), and 5control subjects. Intergroup differences in GPER score were statistically evaluated. We performed an analysis based on the Visual Analog Scale (VAS). The scoring system evaluates overall pathology (VAS score) based on four distinct components: inflammation, vascular involvement, myopathic changes, and connective tissue alterations. Results: Immunolocalization analysis demonstrated that GPER is constitutively expressed in human skeletal muscle and is upregulated in IM. Enhanced expression included both sarcolemmal and intracellular membrane localization. Notably, GPER upregulation showed a positive correlation with the severity of tissue inflammation. The IM group had significantly higher VAS scores compared to both the N.IM and control groups. Conclusions: We provide the first histopathological characterization of GPER expression in human skeletal muscle. In IM, GPER upregulation may play a protective role by negatively modulating the release of inflammatory mediators, as suggested by experimental evidence from other models of inflammation. The emerging therapeutic development of GPER agonists may represent a promising avenue for the treatment of inflammatory myopathies.